PENGARUH PENGGUNAAN WHATSAPP GROUP TERHADAP PENGETAHUAN WUS TENTANG IVA DI PUSKESMAS PEMBANTU BANDAR KLIPPA TEMBUNG KECAMATAN PERCUT SEI TUAN TAHUN 2020 - Rambe, Rizka Sititah (Jurnal Inovasi Kesehatan Masyarakat, 2021)
Reproductive health is important for everyone. From womb to death. One of the diseases that interfere with the function of the reproductive organs is cervical cancer or cervical cancer. Cervical cancer is uterine cancer that originates from the cervix or cervix that grows and develops from the cervix and grows to the pelvic wall. The beginning of cervical cancer is HPV infection, the pre-cancer stage to cervical cancer takes 10-20 years. Whatsapp is an instant and cross-platform messaging application (mesengger) on smartphones that allows users to send and receive messages such as SMS without using credit but using an internet connection. Knowing the effect of using whatsapp group on women of chieldbearing age knowledge about Inspeksi Visual Asetat. This study used a Quasi Experiment (Quasi-Experiment) method. By using the Pre Test Post Test Control Group Design approach method. Samples A total of 34 were taken with purposive sample technique. It can be seen that from 34 respondents it is known that based on the results of the paired t-test analysis, the t-hit value = 2,690 with a confidence level of 95% (0.05) df = 33 obtained t table (1,865). so t hit table and p value = 0.011 <0.05. So it can be concluded that there is a significant difference in the knowledge of women of childbearing age who do not follow the WhatsApp group with the knowledge of women of childbearing age who participate in the Whatsspp group. The knowledge of women of childbearing age who follow the Whatsapp group is better, which means that the Whatsapp group has been given information about visual acetate inspection (IVA). For this reason, new innovations are needed in providing information to increase knowledge of women of childbearing age about visual acetate inspection (IVA). Keywords: Whatsapp, Knowledge, IVA